Answer:
8 and 14
Step-by-step explanation:
X + Y = 22
X= 22-Y
4X= 7Y
4(22-Y) = 7Y
88-4Y=7Y
88= 11Y
8=Y
X= 22-Y= 22-8=14
<span>
</span>
You can use (a+b)2 = a2+2ab+b2.
(2x - 3)2 = (2x)2 + 2(2x)(-3) + (-3)2 = 4x2 - 12x + 9
Or you can use FOIL.
(2x - 3)2 = (2x - 3)(2x - 3) = (2x)2 + (2x)(-3) + (-3)(2x) + (-3)2 = 4x2 - 12x + 9
hope I could be helpful
<h3>
Answer: A and B (first answer choice)</h3>
Explanation:
Both figures shown in A and B are triangular pyramids. The base is a triangle, and the lateral sides are also triangles. Another example would be rectangular pyramids where the base is a rectangle, and the lateral sides are triangles.
Choice C is ruled out because cones aren't considered pyramids.
Choice D is a combination of a rectangular prism, and a rectangular pyramid stacked on top, so it's not purely a pyramid only. We can rule out choice D.
#2 10:20 of that helps can u help me on my question
Answer:
(0,6)
Step-by-step explanation:
The given system of equations is
![y = \frac{3}{2}x + 6](https://tex.z-dn.net/?f=y%20%3D%20%20%5Cfrac%7B3%7D%7B2%7Dx%20%2B%206)
and
![\frac{1}{2}y - \frac{1}{4}x = 3](https://tex.z-dn.net/?f=%20%5Cfrac%7B1%7D%7B2%7Dy%20-%20%20%5Cfrac%7B1%7D%7B4%7Dx%20%3D%203)
We substitute the first equation into the second equation to get:
![\frac{1}{2} ( \frac{3}{2}x + 6) - \frac{1}{4}x = 3](https://tex.z-dn.net/?f=%20%5Cfrac%7B1%7D%7B2%7D%20%28%20%5Cfrac%7B3%7D%7B2%7Dx%20%2B%206%29%20-%20%20%5Cfrac%7B1%7D%7B4%7Dx%20%3D%203)
We expand to get:
![\frac{3}{4} x + 3 - \frac{1}{4}x = 3](https://tex.z-dn.net/?f=%20%5Cfrac%7B3%7D%7B4%7D%20x%20%2B%203%20-%20%20%5Cfrac%7B1%7D%7B4%7Dx%20%3D%203%20)
We group similar terms to get:
![\frac{3}{4}x - \frac{1}{4}x = 3 - 3](https://tex.z-dn.net/?f=%20%5Cfrac%7B3%7D%7B4%7Dx%20-%20%20%5Cfrac%7B1%7D%7B4%7Dx%20%3D%203%20-%203)
![\frac{1}{2}x = 0](https://tex.z-dn.net/?f=%20%5Cfrac%7B1%7D%7B2%7Dx%20%3D%200)
![x = 0](https://tex.z-dn.net/?f=x%20%3D%200)
Put x=0 in to the first equation to get:
![y = 6](https://tex.z-dn.net/?f=y%20%3D%206)
Therefore the solution is (0,6)